Personal Identity Economics: Facebook and the Distortion of Identity Politics. (May 2021) - Lim, Elisha
This article examines Facebook's role in the treatment of marginalized identity as currency. Recent examples of solidarity statements and corporate social responsibility rhetoric treat disenfranchised racial and gender identities as value-added competitive market quantities to boost brands. This trend also incentivizes marginalized actors to capitalize on their own disenfranchisement in pursuit of visibility and career advancement. The resulting identity politicking replaces communal care, grassroots social ties, solidarity, and interdependence with isolating market competition. This article diverges from scholars who trouble the differential value of identity—by troubling the valuation of identity itself. Facebook normalizes identity as private property in what I call a transition from identity politics to "personal identity economics." I coin this concept and break it down into the following four factors: (1) The optimization of difference beginning in the 1970s, (2) Facebook's algorithmic invasion of market logic into intimate aspects of life starting in the mid 2000s, (3) Ads Manager's economization of identity into legible economic units, and (4) neoliberal corporate social responsibility rhetoric of "social good" as a profitable asset.